The Influence of AIMOHit to Medication Adherence of Hypertension Patients in Malang - Alfrina Hany; Klara Yunita Inuq Thomas; Ahmad Hasyim Wibisono (Journal of Nursing Science Update (JNSU), 2021)
The long-term treatment that a hypertensive patient has to undergo has resulted in the patient becoming non-adherent. Patients accidentally not taking medication is one of the causes of non-adherence. A method for preventing non-compliance due to forgetting to take medication is important. The AIMOHit application which means "Let's Remember to Take Hypertension Medication" is designed to support hypertensive patients to be compliant in taking medication. This study aims to identify the effect of AIMOHit application on adherence to taking medication for hypertensive patients in the Janti Health Center, Malang City. A total of 52 hypertensive patients were willing to be the sample in this study. The instrument used was the AIMOHit application on the Android smartphone for the treatment group and the checklist for the control group. It is known that the adherence statistical test showed that the average adherence to taking medication in the treatment group was higher (32.17) than the control group (20.83). Meanwhile, the Mann Whitney test results obtained p value = 0.000 (<0.05). The conclusion is that there is a significant effect of AIMOHit application on compliance with taking medication for hypertension sufferers in the Janti Health Center, Malang City.